Beyond band of brothers - Winters, Richard D. (Berkley Caliber, 2008)
The commander of Easy Company provides a firsthand memoir of combat during World War II, describing the role of the "Band of Brothers" during the D-Day invasion, the march into Germany, and the liberation of an S.S. death camp.